Dynamics of Free-Living and Attached Bacterial Assemblages in Skeletonema sp. Diatom Cultures at Elevated Temperatures - Deng, Zichao; Chen, Shouchang; Zhang, Ping; Zhang, Xu; Adams, Jonathan M.; Luo, Qiaoqi; Lin, Xin (Frontiers in Marine Science, 2021)
In the context of global warming, changes in phytoplankton-associated bacterial communities have the potential to change biogeochemical cycling and food webs in marine ecosystems. Skeletonema is a cosmopolitan diatom genus in coastal waters worldwide. Here, we grew a Skeletonema strain with its native bacterial assemblage at different temperatures and examined cell concentrations of Skeletonema sp. and free-living bacteria, dissolved organic carbon (DOC) concentrations of cultures, and the community structure of both free-living and attached bacteria at different culture stages. The results showed that elevated temperature increased the specific growth rates of both Skeletonema and free-living bacteria. Different growth stages had a more pronounced effect on community structure compared with temperatures and different physical states of bacteria. The effects of temperature on the structure of the free-living bacterial community were more pronounced compared with diatom-attached bacteria. Carbon metabolism genes and those for some specific amino acid pathways were found to be positively correlated with elevated temperature, which may have profound implications on the oceanic carbon cycle and the marine microbial loop. Network analysis revealed evidence of enhanced cooperation with an increase in positive interactions among different bacteria at elevated temperature. This may help the whole community to overcome the stress of elevated temperature. We speculate that different bacterial species may build more integrated networks with a modified functional profile of the whole community to cope with elevated temperature. This study contributes to an improved understanding of the response of diatom-associated bacterial communities to elevated temperature.